Non-invasive Brain Stimulation in Pediatric Migraine: A Perspective From Evidence in Adult Migraine - Brighina, Filippo; Raieli, Vincenzo; Messina, Luca Maria; Santangelo, Giuseppe; Puma, Domenico; Drago, Flavia; Rocchitelli, Lucia; Vanadia, Francesca; Giglia, Giuseppe; Mangano, Salvatore (Frontiers in Neurology, 2019)
Pediatric migraine remains still a challenge for the headache specialists as concerns both diagnostic and therapeutic aspects. The less ability of children to describe the exact features of their migraines and the lack of reliable biomarker for migraine contribute to complicate the diagnostic process. Therefore, there’s need for new effective tools for supporting diagnostic and therapeutic approach in children with migraine. Recently, promising results have been obtained in adult headache by means of application of neurostimulation techniques boths for investigating pathophysiological mechanisms and also for therapeutical applications. Non invasive brain stimulation (NIBS) techniques like transcraanial magnetic stimulation (TMS) and transcranial direct current stimulation (tDCS) indeed proved to be generally safe and showing also some evidence of efficacy particularly for the symptomatic treatment. On such basis, in the last years increasing interest is rising in scientific pediatric community to evaluate the potential of such approaches for treatment pediatric headaches, particularly in migraine. Here we present a perspective for application of TMS and tDCS technique in children migraine principally based on evidence coming by studies in adults.